Making use of transcription data from qualitative research within a corpus-linguistic paradigm: issues, experiences and recommendations. Issue 1 (April 2022) - Collins, Luke; Hardie, Andrew
Abstract : In this paper, we reflect on the process of re-operationalising transcript data generated in an ethnographic study for the purposes of corpus analysis. We present a corpus of patient–provider interactions in the context of Emergency Departments in hospitals in Australia, to discuss the process through which ethnographic transcripts were manipulated to generate a searchable corpus. We refer to the types of corpus analysis that this conversion enables, facilitated by the rich metadata collected alongside the transcribed audio recordings, augmenting the findings of prior qualitative analyses. Subsequently, we offer guidance for spoken data transcription, intended to 'future proof' such data for subsequent reformatting for corpus linguistic analysis.